(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. The aim of the current meta-analysis was to assess the predictive value of blood fibroblast growth factor 23 (FGF-23) for acute kidney injury (AKI) in adult patients. Methods. We retrieved relative publications from electronic databases including the Cochrane Library, PubMed, Google Scholar, Scopus, web of science, and Wanfang Data from their inception to Aug 2022. Results. This meta-analysis study included seven prospective cohort trials comprising 1,655 adult patients. The overall pooled area under the receiver operating characteristic curve (AUC) from seven studies was 0.83 (95% CI: 0.80 to 0.86). Significant heterogeneity was identified (Q = 9.82, P = .004, I2 = 80). Pooled sensitivity and specificity were 0.75 (95% CI: 0.59 to 0.87) and 0.77 (95% CI: 0.65 to 0.87), respectively. Pooled positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were 3.3 (95% CI: 1.8 to 6.3), 0.32 (95% CI: 0.16 to 0.63), and 10 (95% CI: 3 to 38); respectively. Moreover, our sensitivity analysis showed that when a trial from Asia was excluded, the predictive value of FGF-23 was declined. Conclusion. Our results of meta-analysis of seven prospective cohort trials suggested that blood FGF-23 is a candidate indicator for the prediction of AKI in adult patients. Results of future large and well-designed clinical trials are still needed. DOI: 10.52547/ijkd.7189